2004
DOI: 10.1161/01.cir.0000124231.98250.a8
|View full text |Cite
|
Sign up to set email alerts
|

Myocyte Nitric Oxide Synthase 2 Contributes to Blunted β-Adrenergic Response in Failing Human Hearts by Decreasing Ca 2+ Transients

Abstract: Background-Human heart failure (HF) usually exhibits blunted response to ␤-adrenergic receptor (AR) stimulation.Here, we examined whether expression of nitric oxide synthase-2 (NOS2, or inducible NOS) contributes to this loss of inotropic reserve in human HF. Methods and Results-Failing human hearts were obtained at transplantation. Contraction and [Ca 2ϩ ] i measurements were performed in isolated cardiac myocytes and trabeculae. In HF myocytes and muscle, isoproterenol (ISO), a ␤-AR agonist, led to small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 43 publications
4
57
0
2
Order By: Relevance
“…However, a coherent hypothesis detailing the role of specific NOS isoforms and the locus of action of NO in heart failure has not yet emerged. Some studies indicate that cytokine-induced NOS2 and NO production cause suppression of myocyte Ca 2ϩ transients (35)(36)(37)(38). However, it has more recently been shown that constitutive NOS isoforms contribute to the heart failure phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, a coherent hypothesis detailing the role of specific NOS isoforms and the locus of action of NO in heart failure has not yet emerged. Some studies indicate that cytokine-induced NOS2 and NO production cause suppression of myocyte Ca 2ϩ transients (35)(36)(37)(38). However, it has more recently been shown that constitutive NOS isoforms contribute to the heart failure phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The biphasic nature of SIN-1 may relate to the physiological regulation of basal and submaximal β-adrenergic-stimulated contractility with low peroxynitrite production (i.e., NOS1) [40], and the pathophysiological regulation of chronic β-adrenergic stimulation with high peroxynitrite production (i.e., NOS2), as occurs in heart failure [3]. Thus, it appears that low SIN-1 may potentially mimic the peroxynitrite production of NOS1, which is hypothesized to produce low concentrations of peroxynitrite due to a co-localization with xanthine oxidase [4].…”
Section: Sin-1 and Plb −/− Myocyte Functionmentioning
confidence: 99%
“…NOS1 is considered a physiological regulator of cardiac function and is also thought to increase myocardial contractility [41]. Conversely, high SIN-1 may be mimicking the peroxynitrite production of NOS2, which is considered to be a pathophysiological regulator of cardiac function by reducing β-adrenergic responsiveness [3,36]. During many pathophysiological conditions of the myocardium, nitric oxide production is increased with NOS2 expression [3,42] and superoxide production is increased through NADPH oxidase and/or xanthine oxidoreductase [8,9], leading to supraphysiological peroxynitrite production and cardiac dysfunction.…”
Section: Sin-1 and Plb −/− Myocyte Functionmentioning
confidence: 99%
See 2 more Smart Citations